Gender Variation in the Emotional Construal of Russian Journalistic Non-fiction - Šipka, Danko (Poznańskie Studia Slawistyczne, 2015)
The author analyzes gender differences in the Russian journalistic discourse using the example of the lexical field related to the concept of грусть ‘sorrowʼ. The more frequent use of these words is indicative of a higher level of empathy. The results demonstrate that male authors exhibit a high er proclivity towards the usage of the words from the aforementioned lexical field. The results are another piece of evidence that a higher level of empathy in women is not absolute but rather highly dependent on the concrete context.